2021
DOI: 10.3390/molecules26082162
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Targeted Alpha-Particle-Emitting Radiopharmaceuticals as Treatments for Prostate Cancer Patients with Bone Metastases

Abstract: Bone metastasis remains a major cause of death in cancer patients, and current therapies for bone metastatic disease are mainly palliative. Bone metastases arise after cancer cells have colonized the bone and co-opted the normal bone remodeling process. In addition to bone-targeted therapies (e.g., bisphosphonate and denosumab), hormone therapy, chemotherapy, external beam radiation therapy, and surgical intervention, attempts have been made to use systemic radiotherapy as a means of delivering cytocidal radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 128 publications
0
1
0
Order By: Relevance
“…Nuclear imaging using radioisotopes is essential in diagnosis, allowing early detection of metastatic lesions in bone, often 6 mo or more before X-ray findings[ 19 ]. Therefore, timely nuclear imaging is essential for PC patients, as it can help physicians to identify bone metastases in time, develop more effective treatment strategies, and improve treatment outcomes and survival rates[ 20 ]. 99mTc-MDP SPECT/CT imaging is a nuclear medicine imaging technique for the detection of bone diseases and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear imaging using radioisotopes is essential in diagnosis, allowing early detection of metastatic lesions in bone, often 6 mo or more before X-ray findings[ 19 ]. Therefore, timely nuclear imaging is essential for PC patients, as it can help physicians to identify bone metastases in time, develop more effective treatment strategies, and improve treatment outcomes and survival rates[ 20 ]. 99mTc-MDP SPECT/CT imaging is a nuclear medicine imaging technique for the detection of bone diseases and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, addition of the anti-IL-6 monoclonal Ab (mAb), siltuximab (CNT0238) to mitoxantrone/prednisone, reduced expression of IL-6-regulated genes and suppressed known IL-6 signalling pathways including JAK-STAT3 and ERK1/2, but there was no improvement in outcomes for patients with mCRPC [ 34 ]. Despite promising efficacy of a CCL2 mAb in rodent models of prostate cancer, sustained suppression of serum CCL2 concentrations was not achieved in patients with mCRPC [ 83 ]. A randomized phase Ib/II study (MAGIC-8; NCT03689699) evaluating the effects of nivolumab with or without the IL-8 mAb (BMS-986253), which signals via the chemokine receptors, CXCR1 and CXCR2 [ 100 ], in combination with a short course of androgen deprivation therapy in men with castration-sensitive prostate cancer, is currently under investigation.…”
Section: Prostate Cancer Metastasis To Bonementioning
confidence: 99%
“…Several radiopharmaceutical conjugates have been tried and proved to be effective in treating bone metastases [5][6][7] and metastasized castration-resistant prostate cancer in recent decades (mCRPC). In addition, various research on the therapeutic use of α-emitter radiopharmaceuticals have been published, and several writers have indicated that they are preferable in terms of therapy [8][9][10][11][12][13][14][15][16]. Targeted alpha treatment targets cancer cells and the tumor microenvironment while limiting damage to adjacent organs.…”
Section: Introductionmentioning
confidence: 99%